Incorporating changeable attitudes toward vaccination into compartment models for infectious diseases - Yi Jiang; Kristin M. Kurianski; Jane HyoJin Lee; Yanping Ma; Daniel Cicala; Glenn Ledder (Mathematical Biosciences and Engineering)
We develop a mechanistic model that classifies individuals both in terms of epidemiological status (SIR) and vaccination attitude (Willing or Unwilling/Unable), with the goal of discovering how disease spread is influenced by changing opinions about vaccination. Analysis of the model identifies the existence and stability criteria for both disease-free and endemic disease equilibria. The analytical results, supported by numerical simulations, show that attitude changes induced by disease prevalence can destabilize endemic disease equilibria, resulting in limit cycles.